Context, word, and student predictors in second language vocabulary learning. (31st October 2018) - MULDER, EVELIEN; VAN DE VEN, MARCO; SEGERS, ELIANE; VERHOEVEN, LUDO
ABSTRACT: We examined to what extent the variation in vocabulary learning outcomes (vocabulary knowledge, learning gain, and rate of forgetting) in English as a second language (L2) in context can be predicted from semantic contextual support, word characteristics (cognate status, Levenshtein distance, word frequency, and word length), and student characteristics (prior vocabulary knowledge, reading ability, and exposure to English) in 197 Dutch adolescents. Students were taught cognates, false friends, and control words through judging sentences with varying degrees of semantic contextual support using a pretest/posttest between subjects design. Participants were presented with an English target word and its Dutch translation, followed by an English sentence. They were instructed to judge the plausibility of the sentence. Mixed-efffects models indicated that learning gains were higher for sentences with more semantic contextual support and in students with stronger reading comprehension skills. We were the first to show that Levenshtein distance is an important predictor for L2 vocabulary learning outcomes. Furthermore, more accurate as well as faster learning task performance lead to higher learning outcomes. It can thus be concluded that L2 study materials containing semantically supportive contexts and that focus on words with little L1-L2 overlap are most effective for L2 vocabulary learning.